The Sixth Edition of the WHO laboratory manual for the examination and processing of human semen: is everything new a well-forgotten old? - Yu. V. Olefir; I. V. Vinogradov; M. A. Rodionov; A. R. Zhyvulko; D. M. Popov; D. M. Monakov (Вестник урологии)
Despite many shortcomings, the semen analysis remains the leading method of male fertility assessment. For several decades, the WHO has been working on standardisation of the methodology for examining human ejaculate. In 2021, the sixth edition of WHO laboratory manual for the examination and processing of human semen was released, which proposed several concepts for performing and interpreting the results of a semen analysis. Many of these concepts are not new and have already been covered in previous tutorials. At the same time, the rejection of reference values and the transition to “decision limits” raises several questions that have not yet been answered.